New Developments on Ostrowski Type Inequalities via q-Fractional Integrals Involving s-Convex Functions. (13th October 2022) - Wang, Xiaoming; Khan, Khuram Ali; Ditta, Allah; Nosheen, Ammara; Awan, Khalid Mahmood; Mabela, Rostin Matendo
Abstract : In the present paper, q -fractional integral operators are used to construct quantum analogue of Ostrowski type inequalities for the class of s -convex functions. The limiting cases include the nonfractional existing cases from literature. Specially, Ostrowski type inequalities for q -integrals and Ostrowski type inequalities for convex functions are deduced.